Tracheobronchography and balloon dilatation in acquired neonatal tracheal stenosis. Issue 1 (January 1995) - Bétrémieux, P.; Tréguier, C.; Pladys, P.; Bourdinière, J.; Leclech, G.; Lefrancois, C.
Abstract : Between 1988 and 1992, 18 mechanically ventilated newborn babies (mean weight 1300 g and gestational age 30 weeks) presented with deteriorating respiratory failure at a mean age of 29 days. All developed increased oxygen requirements, hypoxic and hypercapnic episodes, and radiological changes of fixed lobar emphysema or recurrent atelectasis which sometimes changed sides from one day to another. Tracheobronchography with iopydol-iopydone was normal in five (27%) cases, but in 13 showed tracheobronchial stenosis localised to the lower trachea (seven cases), to the right main bronchus (three cases), or including the left main bronchus (four cases). Eleven of these 13 patients underwent endoscopy and balloon dilatation of the stenotic area. Five patients died, one before endoscopy, one immediately after endoscopies, and three subsequently with severe bronchopulmonary dysplasia. The other six babies recovered without any sequelae after balloon dilatation.